Customer satisfaction is not enough: examining the weak link between digital service strategies and customer loyalty - Indah Julianti; Suhardi Suhardi; Nelly Astuti (Economic: Journal Economic and Business, 2026)
This study aims to analyze the influence of CRM personalization, service responsiveness, and omnichannel integration on customer loyalty, with customer satisfaction as a mediating variable in digital businesses. The study used a quantitative approach with the PLS-SEM method. The results showed that all three variables have a positive and significant effect on customer satisfaction, but do not have a significant direct effect on customer loyalty. Customer satisfaction also cannot significantly mediate the relationship. These findings indicate that digital service strategies are not sufficient to build sustainable customer loyalty without the support of relational factors such as trust and emotional engagement. This study implies that digital businesses need to develop deeper customer relationships to increase customer loyalty.